The Consequences of Landscape Fragmentation on Socio-Ecological Patterns in a Rapidly Developing Urban Area: A Case Study of the National Autonomous University of Mexico - Zambrano, Luis; Aronson, Myla F. J.; Fernandez, Tania (Frontiers in Environmental Science, 2019)
Fragmentation of natural landscapes during urbanization processes has been well linked to biodiversity loss and changes in ecological and ecosystem function. Fragmentation can also have profound effects on provision of ecosystem services and on human social dynamics and well-being within cities. The ways in which ecological, ecosystem service, and social factors and the interactions among these are affected by fragmentation is not well studied. Understanding these relationships is particularly important in cities where high densities of human population create intense and dynamic interactions within green spaces. Using the rapidly developing campus of the National Autonomous University of Mexico (UNAM) in Mexico City as a case study, we examine the effects of natural area fragmentation over time on ecosystem services, human well-being, and biodiversity. We compare fragmentation of the campus natural areas between 1954-2015 to non-native plant species distribution maps, models of water infiltration, and mobility and citizen-science data. We found that the loss and fragmentation of the campus’s natural areas from has had varied effects on ecosystem services, and negative effects on human well-being and biodiversity. The relationships between fragmentation and ecosystem services depends on the ecosystem service being measured; water infiltration was negatively impacted by fragmentation but engagement with biodiversity was greatest in areas with a mix of natural and urban land covers. Our human well-being variable, mobility (the average travel time within the campus of walkers, bicyclists, and cars), was negatively affected by fragmentation. Walkers and cyclists spend significantly more time traveling across campus in 2015 compared to 1954. Finally, the most fragmented areas of the campus’s natural areas support large populations of invasive exotic species, indicating negative effects of fragmentation on biodiversity. Although campus urban development is necessary for supporting the academic community at this growing university, we suggest a renewed focus on sustainable campus development in which land sparing in emphasized; connecting instructional, research, administrative and other campus facilities within urban clusters and providing sustainable transport systems. Thus, eliminating further loss and fragmentation of the natural areas on campus, supporting both human well-being and the unique biodiversity of the region.